Pengembangan Media Pembelajaran Matematika Berbantuan Geogebra Materi Volume Kubus dan Balok - Erisa Luthfiah Ananda (Fakultas Keguruan Dan Ilmu Pendidikan, 2025)
The use of technology in mathematics learning is still on minimum utilization. Teachers used to present the material by using PowerPoint is instead of the whiteboard. In other side, mathematics is an abstract lesson which is in the learning process required a medium to visualization the abstract. This research aims to develop geogebra-assisted learning media. The method used in this research is research and development (R&D) with 4D model. The research results show that the learning media that has been developed meets the criteria of being valid, practical with a percentage of 96% in the good category, and is effective in obtaining a Sig value. (2-tailed) is 0.000, which is less than 0.05. It can be concluded that there is a difference in the average results of the pretest and posttest so that there is an influence of the use of media in learning in increasing students' understanding and learning media can be said to be effective.
Reuploud Repository hasyim Mei 2026
Keywords: Development; Geogebra; Cube and Cuboid.